Fecal Bile Acids in Canine Chronic Liver Disease: Results from 46 Dogs - Verena Habermaass; Francesco Bartoli; Eleonora Gori; Rebecca Dini; Aurora Cogozzo; Caterina Puccinelli; Alessio Pierini; Veronica Marchetti (Animals)
The concentrations of fecal and serum bile acids (BAs) are known to be altered in human patients with chronic liver diseases (CLDs), especially those with biliary tract involvement (BTD). Scarce literature is available regarding fecal BA modifications during canine CLDs. This study aimed to evaluate fecal BAs in canine CLDs according to different clinical and clinicopathological variables. Forty-six dogs were enrolled. Canine feces were analyzed by HPLC. Cholic Acid (CA), Chenodeoxycholic Acid (CDCA), Ursodeoxycholic Acid (UDCA), Deoxycholic Acid (DCA), and Lithocholic Acid (LCA) were measured, and primary BAs (CA + CDCA), secondary BAs (UDCA + DCA + LCA), and the primary/secondary (P/S) ratio were calculated. Primary BAs (p < 0.0001), CA (p = 0.0003), CDCA (p = 0.003), the P/S ratio (p = 0.002), and total BAs (p = 0.005) were significatively higher in BTD dogs (n = 18) compared to in non-BTD dogs (n = 28). Fecal secondary BAs did not statistically differ between BTD and non-BTD dogs. Gastrointestinal clinical signs (p = 0.028) and diarrhea (p = 0.03) were significantly more prevalent in BTD dogs compared to in non-BTD dogs, supporting the hypothesis of some pathological mechanisms assimilable to bile acid diarrhea (BAD). Our results could reflect imbalances of the fecal BA metabolism in dogs with CLDs. Further studies involving gut microbiome and metabolomic assessment are needed to better understand the possible clinical implications of BA metabolism disruption and their potential role in canine CLDs.